Improving Vocabulary Mastery Using Selected Game: Colour Me Colours for EYL Students - Nuridah Nuridah; M Dahlan Bahang; Fitri Arniati (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
The mastery of vocabulary is important and it is a fundamental requirement that influences students’ achievement in studying English. However, during the pre-observation, most of students still have a problem with vocabulary mastery. They are difficult to join the lesson well in the classroom, although the teacher explains the material clearly, this seems because they lack of vocabulary. This article aimed to find out whether the selected game i.e., “Colour Me Colours” can improve the students’ vocabulary mastery at the Second-grade of SMP YP PGRI 4 Makassar. This pre-experimental involves one pre-test and post-test group with four meetings of treatment between it. The data was collected through vocabulary tests to find out students’ scores. Derived from the data analyzed, “Colour Me Colours” game can improve the students’ vocabulary mastery. The students’ scores had a significant different score in pre-test and post-test. The result of the pre-test (49) was low than post-test (90,66). This result highlighted significant findings that most students were more active and interested in learning vocabulary by using “Colour Me Colours” game.